1993
DOI: 10.3171/jns.1993.78.4.0669
|View full text |Cite
|
Sign up to set email alerts
|

Compression of the C-2 root by a rare anomalous ectatic vertebral artery

Abstract: The authors report a symptomatic congenitally anomalous ectatic vertebral artery not passing through the transverse foramen of the atlas (C-1), but instead piercing the dura mater below the posterior arch of the C-1 in the atlantoaxial (C1-2) interlaminar space. This occurrence is exceptionally rare, but in this case it was uniquely associated with occipital neuralgia due to vascular compression of the C-2 root. Microvascular decompression was curative. Neuroradiological and surgical findings are presented and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(32 citation statements)
references
References 5 publications
2
28
0
2
Order By: Relevance
“…Tortuosity of the VA, in particular, has been shown to produce extradural cervical radiculopathy as well as intradural brainstem dysfunction by direct compression. 1,6,7,[9][10][11][12][13][17][18][19][20]23,25,29,30 Such tortuosity has been observed postmortem in anatomical studies, as well as in vivo on radiography, MRI, or via traditional angiography. 2,5,28,35 Classically, Jannetta linked vascular compression of the trigeminal nerve to trigeminal neuralgia, and showed that microvascular decompression of the affected nerve could produce symptomatic relief.…”
Section: Discussionmentioning
confidence: 99%
“…Tortuosity of the VA, in particular, has been shown to produce extradural cervical radiculopathy as well as intradural brainstem dysfunction by direct compression. 1,6,7,[9][10][11][12][13][17][18][19][20]23,25,29,30 Such tortuosity has been observed postmortem in anatomical studies, as well as in vivo on radiography, MRI, or via traditional angiography. 2,5,28,35 Classically, Jannetta linked vascular compression of the trigeminal nerve to trigeminal neuralgia, and showed that microvascular decompression of the affected nerve could produce symptomatic relief.…”
Section: Discussionmentioning
confidence: 99%
“…A etiologia, nos casos considerados sintomáticos, pode variar de acordo com os segmentos afetados: traumatismos crânio encefálicos 16 e cervicais 17,18 , irritação dos linfonodos cervicais sobre o nervo 19 ; processos inflamatórios ou degenerativos da coluna cervical 17,[20][21][22] ; neurossífilis 23 ; neuroma do nervo occipital maior 24 ; arterite temporal 25 ; estenose foraminal 26 ; malformação de Chiari 27 ; compressão vascular de C2 28,29 ; fibrosites 30 ; meningite 4 ; espasmos musculares 31 ; fraturas não traumáticas de C 3 -C 4…”
Section: Localização Localização Fatores Desencadeantes Tratamentounclassified
“…9 On radiographic imaging it was noted that an ectatic VA was compressing the exiting nerve root at C1-2. A posterior MVD was conducted, with the placement of an oxidized cotton plug to separate the exiting root from the vessel.…”
Section: -9mentioning
confidence: 99%